PENERAPAN LITERASI NUMERASI PEMBELAJARAN KONSTEKTUAL BERBASIS SUPERMARKET TOUR DI SUPERINDO PADA SISWA KELAS II MINU UNGGULAN SUKOREJO BOJONEGORO - Eka Wahyuningtyas, Serly; Rahma Maulida Attaromi, Annisa; Nur Faizah, Wela; Latri Cahyani, Eri; Rahma Dewi, Aura; Nur Cahyani, Frista; Damayanti, Risma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of numeracy literacy through contextual learning based on a supermarket tour among second-grade students at MINU Unggulan Sukorejo in Bojonegoro. The study employed a descriptive qualitative approach with data collection techniques including observation and documentation during the learning process at Superindo. The learning activities were designed through hands-on shopping experiences with a budget of Rp30,000, placing students in real-life situations where they managed money, selected products, and understood the available information. The results of the study indicate that the supermarket tour activity is effective in developing students’ literacy and numeracy skills in an integrated manner. Literacy skills were evident through activities such as reading product labels, understanding prices, following instructions, and verbally sharing experiences. Numeracy skills were evident through activities such as recognizing the value of money, calculating the total purchase amount, and making choices based on a budget limit. The implementation of this contextual learning approach provided a learning experience that encouraged active student engagement and strengthened the connection between academic concepts and everyday life practices.